Determination of Thermal Lens effect by white light interferometry - Tayyara, Duygu Önal; Emir, Ahmet; Saraç, Zehra (My University, 2009)
This paper proposes the characterization of thermal lens by white light interferometry on the Methylene -blue/water solution. Thermal lens effect is determined by local phase, which is obtained by analyzing the thermal lens fringes with single sideband modulation method. © 2009 SPIE. © 2009 Elsevier B.V., All rights reserved.
Optical Measurement Systems for Industrial Inspection VI -- Munich -- 76875
Keywords: Refractive index change; Single sideband modulation algorithm; Thermal lens effect; White light interferometer